ChemInform Abstract: Direct Reductive Deoxygenation of Aryl Ketones Catalyzed by Oxo‐Rhenium Complexes. Issue 32 (August 2015) - Fernandes, Tiago A.; Bernardo, Joana R.; Fernandes, Ana C.
Abstract A diverse range of aryl ketones is efficiently reduced to the corresponding alkanes or a mixture of the alkane and alkene derivatives.